Dynamic patterns of postural sway in ballet dancers and track athletes - Schmit, J. M.; Regis, D. I.; Riley, M. A. (Experimental Brain Research, 2005)
We compared the variability and spatiotemporal profile of postural sway of trained ballet dancers to college varsity track athletes under variations in the availability of vision and rigidity of the support surface. We found no differences between the groups according to the variability measures, but variability increased for both groups with eyes closed and on a foam surface. Recurrence quantification analysis revealed that the postural sway of dancers was less regular (lower recurrence), less stable (lower maxline), less complex (lower entropy), and more stationary (lower absolute trend) than that of track athletes. Dancers, possibly as a result of focused balance training, exhibited different dynamic patterns of postural sway.